Assessing the determinants of healthcare expenditures in single-person households - Aviad Tur-Sinai; Racheli Magnezi; Haya Grinvald-Fogel (BMC, 2018)
Abstract Background The study documents a direct relationship between individuals' health and patterns of healthcare expenditure by isolating single-person households and creating a new reference group in which household healthcare expenditure is based on one person's expenditure patterns in accordance with his or her own state of health. Method The study matched two surveys using Propensity Score Matching based on single-person household, age, and gender. Structural Equation Modeling (SEM) explores paths of relation between the population's income and socioeconomic level and its health self-assessment and expenditure. Results Single-person households' health expenditure increases with age and the differences in most expenditure categories are significant. The current study looks into the direct and indirect effects of income, gender, and SES on health insurance and other out-of-pocket health expenses among single-person households. A direct link exists between income, gender, and socioeconomic status (SES) and several aspects of health expenditure, depending on the specific age group. The indirect effects are attested via health status assessment, in which a negative correlation is found between self-assessed health status and various health-expenditure categories. Conclusions The last-mentioned result may support the general perception that single-person households who feel that they are doing better than their near-equals enjoy better health. This line of inquiry yields a better examination of how a single-person household's state of health affects expenditure patterns without assuming ab initio that expenditure patterns attest to state of health.